2010
DOI: 10.1007/s00737-010-0165-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of premenstrual syndrome and premenstrual dysphoric disorder in a population-based sample

Abstract: The study aimed at assessing the prevalence of premenstrual symptoms and of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) in a population-based sample of women of the entire reproductive age range, as well as to analyse predictors of PMS and PMDD in terms of socio-demographic, health status and health behavioural factors. A set of questions on PMS-based on the premenstrual syndrome screening tool developed by Steiner et al., translated into German and piloted-was integrated into the wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
5
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(150 citation statements)
references
References 36 publications
12
115
5
18
Order By: Relevance
“…However, the year of study has no effect on increasing the frequency of PMS. Studies reported the prevalence of PMS in 10% of 3913 participants [26] and 12% of 2863 participants [27]. In contrast, studies with low sample size have shown the higher frequency of the PMS [28].…”
Section: Interpretation In Light Of Previous Studiesmentioning
confidence: 99%
“…However, the year of study has no effect on increasing the frequency of PMS. Studies reported the prevalence of PMS in 10% of 3913 participants [26] and 12% of 2863 participants [27]. In contrast, studies with low sample size have shown the higher frequency of the PMS [28].…”
Section: Interpretation In Light Of Previous Studiesmentioning
confidence: 99%
“…Up to 30% felt them to be considerably bothersome, whilst a smaller proportion of women (3-8%) who experienced severe and debilitating symptoms, were diagnosed with premenstrual dysphoric disorder (PMDD; American Psychiatric Association, 2013), which is considered a distinct psychiatric disorder (Halbreich et al, 2003;Tschudin et al, 2010;Wittchen et al, 2002). It is not clear however, whether PMS and PMDD are separate entities or whether PMDD is an extreme form of PMS.…”
Section: Premenstrual Dysphorias Are Extremely Common In Large Survementioning
confidence: 99%
“…The most commonly reported psychological symptoms included anger and irritability, mood swings/tearfulness, fatigue/lack of energy and food cravings, whilst physical symptoms include bloating, weight gain and breast tenderness Tschudin et al, 2010). Although the syndrome is not distinguished by a specific set of symptoms, there is a consensus that certain symptoms should be present for 2 or more days during the 14 days prior to menstruation, and subside by the end of the menstrual flow (Halbreich et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…В швейцарском общепопуляционном исследовании [21] выявлено, что 3% женщин репродуктивного возраста имеют критерии для диагностики ПМДР; индийские ис-следователи [22] сообщают о частоте в 6%; сплошное по-пуляционное исследование нигерийских студентов-меди-ков [23] показало, что у 36% респонденток имеются крите-рии для диагностики ПМДР.…”
Section: критерии пмдр в Dsm-5unclassified